Hydrothermal vents supporting persistent plumes and microbial chemoautotrophy at Gakkel Ridge (Arctic Ocean) - Wegener, Gunter; Molari, Massimiliano; Purser, Autun; Diehl, Alexander; Albers, Elmar; Walter, Maren; Mertens, Christian; German, Christopher R.; Boetius, Antje (Frontiers in Microbiology, 2024)
Hydrothermal vents emit hot fluids enriched in energy sources for microbial life. Here, we compare the ecological and biogeochemical effects of hydrothermal venting of two recently discovered volcanic seamounts, Polaris and Aurora of the Gakkel Ridge, in the ice-covered Central Arctic Ocean. At both sites, persistent hydrothermal plumes increased up to 800 m into the deep Arctic Ocean. In the two non-buoyant plumes, rates of microbial carbon fixation were strongly elevated compared to background values of 0.5–1 μmol m−3 day−1 in the Arctic deep water, which suggests increased chemoautotrophy on vent-derived energy sources. In the Polaris plume, free sulfide and up to 360 nM hydrogen enabled microorganisms to fix up to 46 μmol inorganic carbon (IC) m−3 day−1. This energy pulse resulted in a strong increase in the relative abundance of SUP05 by 25% and Candidatus Sulfurimonas pluma by 7% of all bacteria. At Aurora, microorganisms fixed up to 35 μmol IC m−3 day−1. Here, metal sulfides limited the bioavailability of reduced sulfur species, and the putative hydrogen oxidizer Ca. S. pluma constituted 35% and SUP05 10% of all bacteria. In accordance with this data, transcriptomic analysis showed a high enrichment of hydrogenase-coding transcripts in Aurora and an enrichment of transcripts coding for sulfur oxidation in Polaris. There was neither evidence for methane consumption nor a substantial increase in the abundance of putative methanotrophs or their transcripts in either plume. Together, our results demonstrate the dominance of hydrogen and sulfide as energy sources in Arctic hydrothermal vent plumes.